Evaluation of Power Quality Issues in grid Connected PV Systems - Gunjan Varshney; D S Chauhan; M P Dave (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This paper deals with the evaluation of power quality issues in grid connected PV systems. This paper also presents  complete simulation, modeling and control of three phase grid connected solar PV module with Maximum Power Point Tracking. Perturb and Observe (P&O) method has been used for Maximum Power Point Tracking. In the proposed model DC bus voltage control , harmonic mitigation and power factor control are discussed as power quality issues. The simulation results are shown in the graphical waveforms and simulation is performed in MATLAB using SIMULINK environment and PSB toolboxes.